Prevalence of myopic maculopathy among the very old: the ural very old study - Bikbov, Mukharram; Gilmanshin, Timur R.; Kazakbaeva, Gyulli M.; Panda-Jonas, Songhomitra; Jonas, Jost B. (Investigative ophthalmology & visual science, 2024)
To assess the prevalence of myopic macular degeneration (MMD) in very old individuals. The population-based Ural Very Old Study (UVOS) included 1526 (81.1%) of 1882 eligible inhabitants aged ≥85 years. Assessable fundus images were available for 930 (60.9%) individuals (mean age, 88.6 ± 2.7 years). MMD was defined by macular patchy atrophies (i.e., MMD stage 3 and 4 as defined by the Pathologic Myopia Study Group). MMD prevalence was 21 of 930 (2.3%; 95% CI, 1.3-3.3), with 10 individuals (1.1%; 95% CI, 0.4-1.7) having MMD stage 3 and 11 participants (1.2%; 95% CI, 0.5-1.9) MMD stage 4 disease. Within MMD stage 3 and 4, prevalence of binocular moderate to severe vision impairment was 4 of 10 (40%; 95% CI, 31-77) and 7 of 11 (64%; 95% CI, 30-98), respectively, and the prevalence of binocular blindness was 2 of 10 (20%; 95% CI, 0-50) and 3 of 11 (27%; 95% CI, 0-59), respectively. In minor myopia (axial length, 24.0 to <24.5 mm), moderate myopia (axial length, 24.5 to <26.5 mm), and high myopia (axial length, ≥26.5 mm), MMD prevalence in the right eyes was 0 of 46 eyes (0%), 3 of 40 eyes (8%; 95% CI, 0-16), and 7 of 9 (78%; 95% CI, 44-100), respectively; MMD prevalence in the left eyes was 1 in 48 eyes (2%; 95% CI, 0-6), 4 of 36 eyes (11%; 95% CI, 0-22), and 3 of 4 eyes (75%; 95% CI, 0-100), respectively. In multivariable analysis, a higher MMD prevalence (odds ratio, 8.89; 95% CI, 3.43-23.0; P < 0.001) and higher MMD stage (beta, 0.45; B, 19; 95% CI, 0.16-0.22; P < 0.001) were correlated with longer axial length but not with any other ocular or systemic parameter. MMD prevalence (stages 3 and 4) in very old individuals increased 8.89-fold for each mm axial length increase, with a prevalence of ≥75% in highly myopic eyes. In old age, highly myopic individuals have a high risk of eventually developing MMD with marked vision impairment.
Gesehen am 22.10.2024